The Impact of Reaction Lights-Based Shadow Training on Foot Agility in Badminton Players at Pelangi Pontianak City - Ade Rahmat; Ashadi Cahyadi (INSPIREE: Indonesian Sport Innovation Review, 2024)
The  purpose  of  the study. The  purpose  of  this  study  was  to find  out  the  effect  of  reaction  light  trainingand  shuttle  run  on  footwork  agility  in  PB  badminton  participants Pelangi Pontianak City. Materials and methods. This  study  uses  this  type  of  experimental  research.  Inthis study there were two groups of experiments that were deliberately given treatment. Results. The analysis's findings for the first test's Lscore test count and the test's final result were Lcalculated, yielding 0.1866<Ltable 0.2287 and 0.1356<Ltable 0.2287. Thus, based on the analysis of this data, preliminary test results and final tests of the normal distribution can be drawn. The sample size of 15, mean 2.75, standard deviation 1.02, and thitung 10.43 are used to determine whether the H0 or Ha hypothesis is accepted in line with the previously given explanation, after which the price calculated and the price of table t are compared. Price comparison between tcalculates to a genuine degree α = 0.05 with degrees of freedom (dk) = (n–1) = 14 and presentil values on the distribution table-t; the result was tcount (10.43)>ttable (1.7613). Conclusions. There is an effect of training using reaction light tools and shuttle  run   exercises   in   improving   the   agility   of   footwork (footwork)   of   PB Pelangi Pontiank City Achievement  with  tCalculate>tTable Can  be  taken  the decision  that  there  is  an  effect  of  training  using  reactionlights  and  shuttle  run exercises in improving.